Regional Aspects of Monetary Policy in Europe - von Hagen, Jürgen; Waller, Christopher J. (Springer US, 2000)
Monetary union has dawned in Europe. Now that the common currency is a reality, questions concerning the practical conduct of monetary policy in the European Monetary Union (EMU) are moving to the forefront of the policy debate. Among these, one of the most critical is how the new monetary union will cope with the large heterogeneity of its member economies. Given the large differences in economic and financial structures among the EMU member states, monetary policy is likely to affect different member economies in different ways. Regional Aspects of Monetary Policy in Europe collects the proceedings of an international conference held at the Center for European Integration Studies of the University of Bonn, dedicated to this issue. The contributions to this conference fall into two parts. The first part consists of empirical and theoretical studies of the regional effects of monetary policy in heterogeneous monetary unions. The second part consists of papers analyzing the political economy of monetary policy in a monetary union of heterogeneous regions or member states. The papers all support the conclusion that regional differences in the responses to a common monetary policy will make European monetary policy especially difficult in the years to come. Such differences arise from a variety of sources, and they cannot be expected to be mere teething troubles that will disappear after a while. Even if they were ignored in the run-up to the EMU, Europe's central bankers and economic policy makers will have to learn how to cope with such differences in the future
Keywords: Europäische Union; Macroeconomics/Monetary Economics//Financial Economics; Political Science; International Economics; Macroeconomics; Political science; International economics; Regionalwirtschaft; Währungsunion; Geldpolitik; Konferenzschrift -- 1998 -- Bonn